Risk and Protective Factors of Psychological Distress in Patients Who Recovered From COVID-19: The Role of Cognitive Reserve - Devita, Maria; Di Rosa, Elisa; Iannizzi, Pamela; Bianconi, Sara; Contin, Sara Anastasia; Tiriolo, Simona; Ghisi, Marta; Schiavo, Rossana; Bernardinello, Nicol; Cocconcelli, Elisabetta; Balestro, Elisabetta; Cattelan, Anna Maria; et al. (Frontiers in Psychology, 2022)
Recent studies reported the development of psychological distress symptoms in recovered COVID-19 patients. However, evidence is still scarce and new data are needed to define the exact risk and, moreover, protective factors that can explain the variability in symptoms manifestation. In the present study, we enrolled 257 patients recovered from COVID-19 and we evaluated the levels of psychological distress through the Symptoms Checklist-90-R scale. Data concerning illness-related variables were collected from medical records, while the presence of subjective cognitive difficulties, both before and after the illness, as well as the level of cognitive reserve were assessed over a clinical interview. Results revealed that being female and reporting the presence of subjective cognitive difficulties after COVID-19 were associated with higher levels of psychological distress. At the same time, being admitted to hospital and having a high cognitive reserve were protective factors. Adding new information in this emerging research field, our results highlight the importance of a complete psychological and cognitive assessment in COVID-19 patients.